PENGARUH PEMASARAN DIGITAL TERHADAP KINERJA UMKM DI KOTA LHOKSEUMAWE DENGAN INOVASI PRODUK SEBAGAI VARIABEL INTERVENING - Muhammad Razie Effendi; Rusydi Abu Bakar; Naufal Bachri (J-MIND (Jurnal Manajemen Indonesia), 2022)
This study examined the effect of digital marketing on marketing performance, and examined the mediating effect of product innovation variable. The sample in this study was 160 entrepreneurs of SME business in Lhokseumawe City who focused on the field of fashion. The analytical tool used is path analysis using the SEM (Structural Equation Modeling) with AMOS. The results showed that digital marketing had a positive and significant effect on marketing performance and the product innovation mediated between the digital marketing variable and the marketing performance.